MODY probability calculator for GCK and HNF1A screening in a multiethnic background population - Tarantino, Roberta Magalhães (2019)
Universidade Federal do Rio de Janeiro. Departamento de Medicina Interna. Seção de Diabetes e Nutrologia. Rio de Janeiro, RJ, Brasil.